Prospects for future economic integration among the League of Arab States - Hamid, Zarinah; Mohd Amin, Ruzita; Md Saad, Norma (2008)
The League of Arab States (LAS) was formed in 1945 with the objective of unifying the Arab countries through political, educational, cultural and economic cooperation. In its efforts to expand the traditional focus of attention beyond political issues, it has placed an equally important attention on economic matters whereby the Economic and Social Council of the League adopted resolution No. 1317 of the 1980 Amman Summit declaring the establishment of a Pan-Arab Free Trade Area. In the light of this recent development, it is therefore, important to first investigate whether or not the LAS possesses the necessary prerequisites for a successful regional trade arrangement. This paper examines the trade structure among five LAS members, namely Egypt, Jordan, Saudi Arabia, Syria and Oman by analyzing their dynamic exports as well as their "trade concentration", and "trade divergence" profiles between the years 1990 and 2003. In general, the findings indicate that the eXisting trade structure may not facilitate intra-regional trade among LAS members. Divergence estimates indicate that only Jordan shows prospects for greater regional exports while the prospects for Egypt, Oman, Saudi Arabia and Syria do not appear to be encouraging. Except for Jordan, exports are found to be highly concentrated especially for Saudi Arabia and Syria. Therefore, based on the findings there is a need for these countries to realign their trade policies in order to promote a more favorable environment for the creation of the Pan-Arab Free Trade Area.